Indigenous knowledge govenance framework : a holistic model for indigenous knowledge management - Tariq, Zaman (Universiti Malaysia Sarawak, (UNIMAS), 2013)
Development organisations acknowledge and recognise the role of Indigenous Knowledge (IK) in solutions to local problems. It is a resource that can help produce more and better food, maintain healthy lives, share wealth, prevent conflict, manage local affairs, and thus contribute to global solutions. As a wide range of digital tools have been developed, researchers and development experts are focusing on how to use information and communication technologies (ICTs) to manage this highly-valued resource. Indigenous knowledge mainly relies on tacit and implicit knowledge forms, which are deeply rooted in the social and cultural context of indigenous communities. However, ICTs for Indigenous Knowledge Management (IKM) have been designed using the conventional approach of creating and manipulating databases of knowledge. This typical approach of IKM generates the issues of indigenous knowledge governance, de contextualisation and data manipulation. Hence, the main research question of the study is “How can we introduce indigenous knowledge governance into ICT-based Indigenous Knowledge Management System (IKMS)?” The investigation was done in three phases: first, we explored the theoretical gaps and the inherent structure of indigenous knowledge management system in communities. Second, we addressed the gaps by modelling IKMS in communities and proposing a structured Indigenous Knowledge Governance Framework (IKGF). Third, we used the framework to model an existing IKMS and then validated the framework by using it as a base for design, development and implementation of ICT-based IKMS.